Revitalizing Internship Registration Portal with an Implementation of Application Lifecycle Management - Bertha Alan Manuel; Oscar Karnalim (SISFORMA, 2018)
Internship is an undergraduate activity for gaining working experiences.  Hence, it is expected that some universities convert it as an undergraduate course. In our university, registering internship topic is automated using a web-based portal; it takes tremendous effort if done manually. Nevertheless, according to our informal survey, existing portal suffers a lot of limitation, resulting user dissatisfaction. This paper presents a further development of such portal by following phases described in Application Lifecycle Management. According to three evaluation scenarios (black-box, small-group user, and large-group user testing), proposed portal works well and fits user need.